2014
DOI: 10.1097/sla.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Gallbladder Cancer at Cholecystectomy

Abstract: Surgeons' suspicion for GBC should be heightened when they are performing or converting from LC to OC and when patients are older, Asian or African American, female, and have an elevated alkaline phosphatase level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 30 publications
3
23
1
2
Order By: Relevance
“…Some investigators suggested iGBC was more likely found in elderly patients, dilated bile duct, and thickened GB wall [ 12 ]. Another retrospective study revealed that advanced age, female sex, Asian or African American ethnicity, an elevated ALP, and converted open cholecystectomy as risk factors [ 10 ]. We found that iGBC patients tend to be older, anemic, and on hypertensive medication compared with benign GB diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators suggested iGBC was more likely found in elderly patients, dilated bile duct, and thickened GB wall [ 12 ]. Another retrospective study revealed that advanced age, female sex, Asian or African American ethnicity, an elevated ALP, and converted open cholecystectomy as risk factors [ 10 ]. We found that iGBC patients tend to be older, anemic, and on hypertensive medication compared with benign GB diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been few reports on the predictive factors of iGBC. A recently published article described old age, female gender, Asian or African American, elevated serum ALP and conversion to open cholecystectomy as risk factors in LC patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Incidental GB cancer, that is cancer detected once a cholecystectomy has been performed, usually for gallstone disease has been reported to range from 0.2% [36] to 0.9% [37]. A study by Fuks and colleagues studied 218 patients with incidental GB cancer: 67 males and 151 females with a median age of 64 years (31 - 88).…”
Section: Resultsmentioning
confidence: 99%
“…18 When discovered intra-operatively, the procedure should be aborted and the patient should be transferred to a hepatobiliary center. Outcomes of patients with an incidental finding of gallbladder cancer have a better prognosis than non-incidentally-discovered disease, provided the patient is staged and managed appropriately with R0 resection.…”
Section: Incidental Gallbladder Carcinomamentioning
confidence: 99%